Flexible S/DPAN/KB Nanofiber Composite as Binder-Free Cathodes for Li-S Batteries - KAHRAMAN, MEMET VEZİR (ELECTROCHEMICAL SOC INC, 2019)
Sulfur/dehydrogenated polyacrylonitrile/ketjen black (S/DPAN/KB) flexible nanofiber composite was prepared by electrospinning technique and tested as a freestanding cathode for high-performance flexible lithium/sulfur batteries. S/PAN/KB was dehydrogenated at 300 degrees C without carbonizing and used as a cathode without any binder/current collector. The SEM observations of the obtained S/DPAN/KB nanofibers showed that the fiber diameters were in a range of 300-600 nm and the sample had a rough surface due to the presence of the S/KB particles. According to the SEM/EDS analysis sulfur is uniformly distributed within PAN fibers in both S/PAN/KB and S/DPAN/KB (heat treated) composites. The prepared binder-free S/DPAN/KB composite cathode exhibited a good electrochemical performance delivering a reversible capacity of 917 mAh g(-1) after 150 cycles, exhibiting a coulombic efficiency about 100%, and demonstrating stable cyclability and good rate capability with a reversible capacity of 342 mA h g(-1) at 1 C. The obtained composite cathode is highly flexible and can be used for LIB powering flexible electronic devices. (C) The Author(s) 2019. Published by ECS.
Keywords: CARBON NANOFIBER; WRAPPED SULFUR; LITHIUM; POLYACRYLONITRILE; ELECTRODES; MECHANISM; NETWORK